A literature review on park-and-rides - Haque, Antora Mohsena; Brakewood, Candace; Rezaei, Shahrbanoo; Khojandi, Anahita (Journal of Transport and Land Use, 2021)
American cities have been implementing park-and-rides (PNRs) since the 1930s; however, there has been a recent resurgence of literature examining this type of transit station. This paper aims to provide a comprehensive review of the current literature on PNRs and directions for future research. PNR studies published in the last ten years were reviewed and text mining was applied to extract key themes. Six themes were identified. The two most common areas of research were network equilibrium and optimization (12 of 37 studies) and demand models (8 of 37 studies). This was followed by guidelines and best practices as well as comparative studies (6 of 37 studies each). Parking utilization had the fewest number of recent studies (3 of 37 studies). This review revealed that the majority of PNR studies were conducted in geographic areas with extensive transit services, most studies have focused on rail-based PNRs, and the most widely used method was multinomial logit. Some areas for future research include studying remote PNRs, examining bus-based PNRs, and assessing the impact of emerging modes on PNR utilization. This systematic review could assist planners and transit agencies in further improving sustainable PNR networks in their cities.